2010
DOI: 10.1248/bpb.33.1574
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Intraocular Pressure by the Instillation of Eye Drops Containing Disulfiram Included with 2-Hydroxypropyl-.BETA.-cyclodextrin in Rabbit

Abstract: Glaucoma is characterized by nerve degeneration that causes the disappearance of retinal ganglion cells, visual field loss and excavation of the optic disk, and ophthalmopathy. 1,2) It is one of the most common causes of visual impairment and blindness throughout the world and is more common in the elderly.3) The major risk factor for glaucoma is elevated intraocular pressure (IOP), which leads to apoptosis and loss of retinal ganglion cells. 4) In treating glaucoma, the focus is on reducing IOP, and retinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In addition, it is known that the increase in IOP in rabbits following the rapid infusion of 5% glucose is caused by a rapid production of aqueous humor, 15) and our previously reports showed that enhanced NO in the aqueous humor causes this increase in IOP using NOS inhibitor, disulfiram (DSF) eye drops. 26) In this study, the NO levels in the aqueous humor increased following the rapid infusion of 5% glucose solution, and the instillation of PGA/HPCD eye drops reduced this increase (Fig. 4, Table 4), and the behavior of IOP and NO levels in rabbit instilled PGA/HPCD eye drops was similar to that instilled DSF eye drops.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, it is known that the increase in IOP in rabbits following the rapid infusion of 5% glucose is caused by a rapid production of aqueous humor, 15) and our previously reports showed that enhanced NO in the aqueous humor causes this increase in IOP using NOS inhibitor, disulfiram (DSF) eye drops. 26) In this study, the NO levels in the aqueous humor increased following the rapid infusion of 5% glucose solution, and the instillation of PGA/HPCD eye drops reduced this increase (Fig. 4, Table 4), and the behavior of IOP and NO levels in rabbit instilled PGA/HPCD eye drops was similar to that instilled DSF eye drops.…”
Section: Discussionsupporting
confidence: 58%
“…4, Table 4), and the behavior of IOP and NO levels in rabbit instilled PGA/HPCD eye drops was similar to that instilled DSF eye drops. 26) The increased IOP and NO levels in rabbits who did receive the 5% glucose infusion were not reduced by instilling the eye drop vehicle (saline containing 0.5% ZnCl 2 and 10% HPCD; data not shown). Thus, we hypothesize that the PGA in the eye drop preparations penetrates the cornea, and may cause a reduction in water production by inhibiting NO production, resulting in a reduction in IOP.…”
Section: Discussionmentioning
confidence: 88%
“…Acetazolamide HPbCD [72][73][74] Anandamides HPbCD [75,76] Cannabinoids (various) HPbCD [77] Ciclosporin aCD [78][79][80] Dehydroepiandrosterone HPbCD [81] Dexamethasone HPbCD, gCD [82][83][84][85][86][87][88] Diclofenac HPbCD, RMbCD [89] Dipivefrine SBEbCD [90] Disulfiram HPbCD [91,92] Dorzolamide RMbCD, gCD [88,93] Enalaprilat HPbCD [94] Enalapril maleate HPbCD [94] Ethoxyzolamide HPbCD [72] Fluorometholone HPgCD [95] Hydrocortisone HPbCD [96,97] Ketoconazole HPbCD [98] Loteprednol etabonate HPbCD, DMbCD [99] Pilocarpine aCD, bCD, HEbCD, HPbCD, SBEbCD [100][101][102][103] Prostaglandins HPbCD [104] Rufloxacin HPbCD [105] Thalidomide HPbCD [106] D 9 -Tetrahydrocannobinol aCD [107,108] Nasal drug delivery: Acyclovir HPbCD [115] 17b-Estradiol DMbCD [116] Insulin aCD, DNaCD, HPaCD, bCD, DMbCD, HPbCD [117] Midazolam SBEbCD [118,…”
Section: Drug Cyclodextrin Referencementioning
confidence: 99%
“…Rapid administration of 15 ml/kg of 5 % glucose intravenously via the marginal ear vein (usually over 20 s) also gives a transient IOP spike [126,127]. Like oral administration of water, this hypotonic solution reduces blood osmolality which leads to transfer of water into the eye.…”
Section: Rabbit Models Of Ocular Hypertensionmentioning
confidence: 99%